PENGARUH DIRECT MARKETING KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN YANG BERDAMPAK PADA MINAT BELI ULANG PRODUK FROZEN FISH UD. KARYA MANDIRI JUWANA - Safitri, Anik Dian; Heri Prabowo; Ika Indriasari (MANAJEMEN, 2024)
The Influence of Direct Marketing on Product Quality and Service Quality on Purchasing Decisions Which Have an Impact on Repurchase Interest in Frozen Fish Ud Products. Karya Mandiri Juwana Management Study Program, PGRI University Semarang 2023. This research aims to measure the influence of direct marketing on product quality and service quality on purchasing decisions which have an impact on interest in repurchasing Frozen Fish Ud products. Juwana's Independent Work This research is a quantitative type of research, namely using a research instrument in the form of a questionnaire which has been prepared into several statements and measured using a 1-5 Likert scale. The population used in this research was UD Frozen fish consumers. Juwana's Independent Work. The sampling technique uses the Cochran formula. The results of the research carried out showed an influence between the variables used.